Pengalaman Hidup Penderita Gout Arthritis pada Lansia di Puskesmas Sentosa Baru Kecamatan Medan Perjuangan - Lestari Lumbanraja, Widia; Simatupang, Lenny Lusia (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Gout arthritis is an inflammation of the joints as a result of metabolic diseases that cannot be excreted through the kidneys in urine excretion so that there is a buildup of Monosodium Urate crystals that cause Hyperuricemia. To find out the life experience of gout arthritis patients in the elderly at the Sentosa Baru Health Center, Medan Perjuangan District. This study uses a qualitative method with a phenomenological method approach using in-depth interviews at the Sentosa Baru Health Center, Medan Perjuangan District, Medan City from August to December 2024. The sample selected by purposive sampling  technique was 10 people. The data analysis technique used in this study is the Miles and Huberman (2014) model with four stages. The participants in this study are 7 (seven) people. The results of this study obtained five themes about the life experiences of gout arthritis patients in the elderly, namely: (1) Physical complaints felt by gout arthritis patients, (2) Experiencing changes in diet and emotions, (3) Undergoing traditional treatment, (4) The importance of family support for treatment motivation and (5) Complications arising from gout arthritis.